Serum concentrations of medroxyprogesterone acetate were undetectable on OPU+5 days and had no effect on the serum progesterone level in patients undergoing the progestin-primed ovarian stimulation protocol - Chen, Xin; Yan, Xu; Xu, Hongyi; Hu, Yueyue; Jiang, Shengfang; Wang, Xiaoning; Peng, Haiying; Feng, Bo; Zhang, Changjun; Diao, Honglu; Zhang, Ying (Frontiers in Endocrinology, 2025)
ObjectiveTo evaluate the dynamics of serum medroxyprogesterone acetate (MPA) concentrations and their influence on serum progesterone (P) levels and pregnancy outcomes in the progestin-primed ovarian stimulation (PPOS) protocol. A total of 116 patients who underwent in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) treatment using the PPOS protocol were included. Serum MPA levels were measured on the third, fifth, and seventh days of MPA use; on the day of human chorionic gonadotropin (hCG) trigger; and two and five days after oocyte pick-up (OPU).ResultsThe serum MPA concentration was 2.26 ± 2.11 nmol/L on the hCG trigger day, 0.37 ± 0.40 nmol/L two days after OPU, and zero five days after OPU. There were no statistically significant differences in P levels on the hCG trigger day, total dosage of Gn, duration of Gn, number of oocytes retrieved, number of mature oocytes, fertilization rate, blastocyst progression rate, CPR, ectopic pregnancy rate, early pregnancy loss rate, or live birth rate (LBR) between the two cohorts (P > 0.05).Conclusion(s)Serum concentrations of MPA had no effect on serum P levels or pregnancy outcomes in patients undergoing the PPOS protocol.